Consumer preferences and trade in genetically modified foods - Pohl Nielsen, Chantal; Thierfelder, Karen; Robinson, Sherman (Elsevier, 2003)
Major agricultural exporters have adopted genetic engineering in agriculture to increase productivity. However, consumers in certain importing countries, particularly the EU and Japan, are wary of these products. In this paper, we analyze the impact of consumer attitudes towards genetically modified (GM) food on global production, prices, and trade patterns. We find that the potential benefits for GM producers depend crucially on consumer willingness to accept these new varieties. If consumers in some countries reject GM foods, then the global benefits from GM products are reduced and distributed differently. Production of non-GM foods may increase, despite the productivity gains in GM varieties." -- Authors' Abstract